Implementation Of Augmented Learning In Improving Student Learning Response PGMI UNIPDU Jombang - Miftakhul Ilmi S. Putra; M. Ansor Anwar; Dhikrul Hakim; Muhammad Syafi’i (Universitas Yudharta Pasuruan, 2020)
This study aims to describe the implementation of augmented learning to improve the response to science learning of class students of PGMI Unipdu Jombang. The research sample was 30 students of class 5A PGMI Unipdu Jombang. The study was conducted in October-December 2019 using an experimental method with data collection techniques through cognitive tests, observation, and interviews. The results showed that augmented learning can improve the learning response of class students of PGMI Unipdu Jombang. Student learning responses to learning science using Augmented learning is positive